The Power of PBL and TPACK: Catalysts for Elevating Students' Writing Learning Outcomes - Lailatul Nurjanah; Laela Hikmah Nurbatra (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
The English writing learning process is crucial in English language education, but it often faces challenges such as limited resources and ineffective teaching methods. To address these issues, this study explores the use of Problem-Based Learning (PBL) integrated with Technological Pedagogical Content Knowledge (TPACK) in the context of English as a foreign language (EFL) learning, specifically in the writing course. The research aims to investigate how the integration of PBL and TPACK can enhance students' writing learning outcomes (assessing their content and clarity, structure of the writing, and language quality). The research follows a Classroom Action Research (CAR) design with a quantitative approach. The subjects consist of 10th-grade students from a public high school in Pasuruan Regency, with a total of 33 participants. Data collection instruments include pre and post writing tests and observation. Data analysis is conducted using Microsoft Excel, employing percentages. The findings demonstrate that the implementation of PBL integrated with TPACK leads to significant improvements in students' writing learning outcomes. In the pre-cycle, the pass percentage was only 39.39%, while in cycle I, it increased to 75.76%, and in cycle II, it reached 93.94%. This study contributes to the development of curricula and teaching methods for English writing. These findings have important implications for future writing instruction that can help improve students' writing learning outcomes. This study’s limitations are constraining the applicability of its findings to diverse educational environments and a relatively brief timeframe. Future research could explore cross-cultural variations, delve into extended research periods, and compare the effectiveness of PBL and TPACK with alternative teaching models in EFL education.